The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 32nd ACM/IEEE International Conference on Software Engineering - Volume 1 2010
DOI: 10.1145/1806799.1806868
|View full text |Cite
|
Sign up to set email alerts
|

A search engine for finding highly relevant applications

Abstract: A fundamental problem of finding applications that are highly relevant to development tasks is the mismatch between the high-level intent reflected in the descriptions of these tasks and low-level implementation details of applications. To reduce this mismatch we created an approach called Exemplar (EXEcutable exaMPLes ARchive) for finding highly relevant software projects from large archives of applications. After a programmer enters a naturallanguage query that contains high-level concepts (e.g., MIME, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 33 publications
0
68
0
Order By: Relevance
“…We assess the efficiency of the engines through the Mean Reciprocal Rank (MRR), a statistical metric used to evaluate a process that produces a list of possible responses to a query [18]. The reciprocal rank of a query is the multiplicative inverse of the rank of the first relevant answer.…”
Section: Rq3: Comparison Against General Search Enginesmentioning
confidence: 99%
“…We assess the efficiency of the engines through the Mean Reciprocal Rank (MRR), a statistical metric used to evaluate a process that produces a list of possible responses to a query [18]. The reciprocal rank of a query is the multiplicative inverse of the rank of the first relevant answer.…”
Section: Rq3: Comparison Against General Search Enginesmentioning
confidence: 99%
“…The terms added can come from a variety of thesauruses [66], rule systems mapping keywords to related terms [28], related Java documentation [41], or from the code the developer is currently writing [12]. For example, Lemos et al [66] found that, when queries were automatically expanded with synonyms from the WordNet [135] thesaurus, it increased recall of CodeGenie [65] by 30% (i.e., query expansion allowed CodeGenie to return more on topic results that otherwise would not have been returned).…”
Section: Improving Ranking Algorithms With Automatic Query Modificationmentioning
confidence: 99%
“…Since programs contain API calls with precisely defined semantics, these API calls can serve as semantic anchors to compute the degree of similarity between requirements and artifacts by matching the semantics of these applications that are expressed with these API calls. Programmers routinely use third-party API calls (e.g., the Java Development Kit (JDK)) to implement various requirements [10,21,30,31,47]. API calls from well-known and widely used libraries have precisely defined semantics-unlike names of program variables, types, and words that programmers use in comments.…”
Section: B Our Hypothesesmentioning
confidence: 99%